Eutectic crystal of L-lysine and plant essential oil active ingredients as well as preparation method and application of eutectic crystal
Through eutectic technology, eugenol and cinnamaldehyde are combined with L-lysine, which solves the poor stability of the active ingredients of plant essential oils and the moisture absorption of L-lysine, achieving higher stability and antibacterial effects, and expanding the application field.
Patent Information
- Application Number
- CN202411607529.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The low melting point and high volatility of plant essential oil active ingredients such as eugenol and cinnamaldehyde lead to poor stability and difficulty in preservation, and L-lysine is prone to moisture absorption, resulting in inconvenience in processing and storage.
Through eutectic technology, the active ingredients of plant essential oils such as eugenol and cinnamaldehyde form stable eutectics with L-lysine, which changes the interaction between molecules and crystal accumulation methods, reduces hygroscopicity and volatility, and enhances stability.
The stability of the active ingredients of plant essential oils and the hygroscopicity of L-lysine is achieved, making eutectics more stable and effective in application, broadening its application field, and significantly improving the antibacterial effect on a variety of bacteria.
Smart Images

Figure BDA0005130008800000051 
Figure BDA0005130008800000061 
Figure BDA0005130008800000062
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of compound co-crystals, and in particular to a co-crystal of L-lysine and an active ingredient of plant essential oil, and a preparation method and application thereof. Background Art
[0002] Eugenol, cinnamaldehyde and other plant essential oil active ingredients are a class of natural antibacterial agents, showing broad-spectrum antibacterial activity and good biodegradability, and are not easy to develop drug resistance. In addition, eugenol and cinnamaldehyde also have antioxidant, antipyretic, anesthetic, insecticidal and other effects, and have broad application prospects in industries such as food, health products, daily chemicals, feed, veterinary drugs, medicine, and pesticides. However, these plant essential oil active ingredients have low melting points and strong volatility, are easily affected by the external environment (light, heat, humidity and air), are not easy to preserve, and cause a large amount of loss of effective ingredients, which is severely limited in practical applications.
[0003] L-lysine is one of the essential amino acids for humans and mammals. It can promote human growth and development, enhance the body's immunity, and also has the effects of promoting animal growth and improving feed utilization. In addition, L-lysine is also a cosmetic nutritional supplement, plant growth regulator, plant protection agent and soil conditioner, and is widely used in feed, food, health products, daily chemicals, pesticides, veterinary drugs, medicine and other fields. However, L-lysine is very easy to absorb moisture, which brings great inconvenience to processing, storage and application. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the objects of the present invention is to provide a co-crystal; the second object of the present invention is to provide a method for preparing the co-crystal; the third object of the present invention is to provide an antibacterial agent; the fourth object of the present invention is to provide the application of the antibacterial agent.
[0005] The basic principle of the present invention is described as follows:
[0006] Cocrystals refer to multi-component crystals with a specific stoichiometric ratio formed by the interaction of active ingredients with other solid small molecules through non-covalent bonds such as hydrogen bonds. Cocrystal technology can improve the physical and chemical properties and enhance the efficacy by changing the interaction between molecules and the crystal stacking mode while retaining the original molecular structure and biological activity of the active ingredients.
[0007] The present invention forms a stable eutectic with active ingredients of plant essential oils such as eugenol and cinnamaldehyde and L-lysine through eutectic technology, which can not only ensure the original efficacy of the active ingredients of the plant essential oils, reduce volatility and enhance stability, but also significantly reduce the hygroscopicity of L-lysine, so that both can better exert their respective efficacy and broaden their application fields.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a co-crystal, comprising the following preparation raw materials: L-lysine and active ingredients of plant essential oils; the molar ratio of L-lysine to the active ingredients of plant essential oils is 1:1; the active ingredients of plant essential oils are at least one of eugenol and cinnamaldehyde.
[0010] Preferably, when the active ingredient of the plant essential oil is eugenol, the co-crystal is a co-crystal of L-lysine and eugenol; the co-crystal of L-lysine and eugenol has diffraction peaks at 2θ values of 4.8±0.2°, 9.8±0.2°, 13.6±0.2°, 14.8±0.2°, 17.5±0.2°, 22.0±0.2°, and 24.9±0.2° in the X-ray powder diffraction spectrum.
[0011] Further preferably, the L-lysine and eugenol co-crystal also has at least one diffraction peak at 2θ values of 10.5±0.2°, 19.8±0.2°, 21.1±0.2°, 21.3±0.2°, 23.6±0.2°, 25.9±0.2°, 31.6±0.2°, and 36.6±0.2° in the X-ray powder diffraction spectrum.
[0012] In some specific embodiments of the present invention, in the composition formed by L-lysine and eugenol, the molar ratio of L-lysine to eugenol can be (1-9):1, wherein a part of the components exist in the form of the L-lysine and eugenol eutectic, and the other part of the components exist in the form of free L-lysine; that is, in addition to the L-lysine and eugenol eutectic described in the present invention, the composition of L-lysine and eugenol may also contain excess L-lysine and other auxiliary materials.
[0013] Preferably, when the active ingredient of the plant essential oil is cinnamaldehyde, the cocrystal is a cocrystal of L-lysine and cinnamaldehyde; the cocrystal of L-lysine and cinnamaldehyde has diffraction peaks at 2θ values of 5.4±0.2°, 8.1±0.2°, 13.7±0.2°, 16.6±0.2°, 19.3±0.2°, 19.8±0.2°, and 22.2±0.2° in the X-ray powder diffraction spectrum.
[0014] Further preferably, the L-lysine and cinnamaldehyde co-crystal also has at least one diffraction peak at 2θ values of 11.0±0.2°, 18.4±0.2°, 20.9±0.2°, 25.2±0.2°, 28.0±0.2°, and 32.8±0.2° in the X-ray powder diffraction spectrum.
[0015] In some specific embodiments of the present invention, in the composition formed by L-lysine and cinnamaldehyde, the molar ratio of L-lysine to cinnamaldehyde can be (1-9):1, wherein a part of the components exist in the form of the L-lysine and cinnamaldehyde eutectic, and another part of the components exist in the form of free L-lysine; that is, in addition to the L-lysine and cinnamaldehyde eutectic described in the present invention, the composition of L-lysine and cinnamaldehyde may also contain excess L-lysine and other auxiliary materials.
[0016] Preferably, when the active ingredients of the plant essential oil are eugenol and cinnamaldehyde, the cocrystal is a cocrystal of L-lysine, eugenol and cinnamaldehyde; the molar ratio of eugenol to cinnamaldehyde is 1:(0.25-4); the cocrystal of L-lysine, eugenol and cinnamaldehyde has diffraction peaks at 2θ values of 4.8±0.2°, 5.4±0.2°, 8.1±0.2°, 14.8±0.2°, 22.0±0.2° and 24.9±0.2° in the X-ray powder diffraction spectrum.
[0017] Further preferably, the L-lysine, eugenol and cinnamaldehyde co-crystal also has at least one diffraction peak at 2θ values of 9.8±0.2°, 10.5±0.2°, 13.7±0.2°, 16.6±0.2°, 17.5±0.2°, 19.3±0.2°, 19.8±0.2°, 21.1±0.2°, 21.3±0.2°, 22.2±0.2°, 23.6±0.2°, 25.9±0.2°, 31.6±0.2°, and 36.6±0.2° in the X-ray powder diffraction spectrum.
[0018] Preferably, the eutectic is in the form of off-white or light yellow powder.
[0019] The second aspect of the present invention provides a method for preparing the co-crystal according to the first aspect of the present invention, wherein the preparation method comprises any one of the following two methods:
[0020] Method 1: mixing the L-lysine and the active ingredient of the plant essential oil under solvent conditions, and collecting the solid by solid-liquid separation to obtain the co-crystal;
[0021] Method 2: Applying mechanical force to make the L-lysine contact and react with the active ingredient of plant essential oil to obtain the co-crystal.
[0022] Preferably, in method 1, the solvent is selected from at least one of water, alcohol solvents, ester solvents, ketone solvents, alkane solvents, aromatic hydrocarbon solvents and halogenated alkane solvents; further preferably, the solvent is selected from at least one of water, methanol, ethanol, isopropanol, ethyl acetate, isopropyl acetate, acetone, methyl tert-butyl ether, n-hexane and n-heptane.
[0023] Preferably, in the method 1, the ratio of the total mass of the L-lysine and the active ingredients of the plant essential oil to the volume of the solvent is 1g:(5-50)mL; further preferably, the ratio of the total mass of the L-lysine and the active ingredients of the plant essential oil to the volume of the solvent is 1g:(5-10)mL.
[0024] Preferably, the method 1 specifically comprises: mixing the L-lysine, the active ingredient of the plant essential oil and a solvent, stirring to obtain a suspension, filtering under reduced pressure, and drying the filter cake to obtain the co-crystal.
[0025] Preferably, the process parameters of the method 1 include: a stirring rate of 200-800 rpm and a stirring time of 2-24 h.
[0026] Further preferably, the process parameters of the method 1 include: a stirring rate of 500-700 rpm and a stirring time of 5-7 h.
[0027] Preferably, in the method 2, the mechanical force is preferably provided by a ball mill, a stirrer, a pulverizer, a mixer or an extruder.
[0028] Preferably, the process parameters of method 2 satisfy at least one of the following:
[0029] 1) Grinding frequency 5-60Hz, grinding time 5-60min;
[0030] 2) Crushing time 1-60min.
[0031] Further preferably, the process parameters of the method 2 satisfy at least one of the following:
[0032] 1) Grinding frequency 15-25Hz, grinding time 25-35min;
[0033] 2) Crushing time 1-3min.
[0034] Preferably, method 2 includes adding a co-solvent; the co-solvent is selected from at least one of alcohol solvents, ester solvents, ketone solvents, alkane solvents, aromatic hydrocarbon solvents and halogenated alkane solvents; further preferably, the co-solvent is selected from at least one of methanol, ethanol, isopropanol, ethyl acetate, isopropyl acetate, acetone, methyl tert-butyl ether, n-hexane and n-heptane.
[0035] Preferably, the method 2 is specifically as follows: adding the L-lysine and the active ingredient of the plant essential oil into a ball mill, a stirrer, a pulverizer, a mixer or an extruder, and using mechanical force to make the L-lysine and the active ingredient of the plant essential oil fully contact and react to obtain the co-crystal.
[0036] The third aspect of the present invention provides an antibacterial agent, comprising the co-crystal described in the first aspect of the present invention.
[0037] The fourth aspect of the present invention provides the use of the antibacterial agent described in the third aspect of the present invention in food, health products, feed, daily chemical products, medicines, and pesticides.
[0038] Preferably, the food may further include a main food ingredient and edible food additives acceptable to food, wherein the food additives include but are not limited to sweeteners, flavoring agents, preservatives, fragrances and coloring agents.
[0039] Preferably, the food includes food and beverage, and the antimicrobial agent is added to the food and beverage in an amount of 0.1-4 mg / mL.
[0040] Preferably, the feed may further include a feed base, and feed adjuvants, wherein the feed base includes but is not limited to soybean meal and hay, and the feed adjuvants include but are not limited to sweeteners, flavoring agents, preservatives, aroma agents and coloring agents.
[0041] Preferably, the antibacterial agent is added to the feed in an amount of 50-200 mg / kg.
[0042] Preferably, the daily chemical products may include daily chemical product main ingredients and daily chemical product additives, and the daily chemical product additives include but are not limited to solvents, flavoring agents, preservatives, flavors and colorants.
[0043] Preferably, the medicines include veterinary medicines and human medicines.
[0044] Preferably, the medicine may further include a pharmaceutically active ingredient and pharmaceutically acceptable excipients, including but not limited to carriers, diluents, adjuvants and colorants.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] 1) The co-crystal provided by the present invention is formed by at least one of eugenol and cinnamaldehyde and L-lysine. The co-crystal has low hygroscopicity and volatility, good stability, and the effective ingredient is not easily lost, which overcomes the defects of single L-lysine having strong hygroscopicity and inconvenient processing and storage, and overcomes the defects of single eugenol or cinnamaldehyde having strong volatility and poor stability. Compared with single eugenol or cinnamaldehyde, the co-crystal shows a lower minimum inhibitory concentration against Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Candida albicans, metronidazole, Aspergillus flavus and other bacteria, and has a better antibacterial effect;
[0047] 2) The method for preparing the cocrystal provided by the present invention has simple steps, good reproducibility, and is suitable for industrial production;
[0048] 3) The antibacterial agent provided by the present invention, based on the antibacterial effect of the co-crystal provided by the present invention, shows excellent antibacterial effect on Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Candida albicans, metronidazole, Aspergillus flavus and other bacteria, and can be applied to food, health products, daily chemicals, feed, veterinary drugs, medicines, and pesticides. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is the X-ray powder diffraction spectrum of the L-lysine and eugenol cocrystal in Example 1;
[0050] Figure 2 is a differential scanning calorimetry analysis diagram of the L-lysine and eugenol cocrystal in Example 1;
[0051] Figure 3 is the Fourier transform infrared spectrum of the L-lysine and eugenol cocrystal in Example 1;
[0052] Figure 4 is the X-ray powder diffraction spectrum of the L-lysine and cinnamaldehyde cocrystal in Example 12;
[0053] Figure 5 is a differential scanning calorimetry analysis diagram of the co-crystal of L-lysine and cinnamaldehyde in Example 12;
[0054] Figure 6 is the Fourier transform infrared spectrum of the L-lysine and cinnamaldehyde cocrystal in Example 12;
[0055] Figure 7 is the X-ray powder diffraction spectrum of the cocrystal of L-lysine, eugenol and cinnamaldehyde in Example 22;
[0056] Figure 8 is an X-ray powder diffraction spectrum of the L-lysine and eugenol co-crystal in Example 1 placed under accelerated stability conditions of 40° C. / 75% RH for 1-3 months;
[0057] Fig. 9 is an X-ray powder diffraction spectrum of the L-lysine and cinnamaldehyde cocrystal in Example 12 placed under accelerated stability conditions of 40° C. / 75% RH for 1-3 months;
[0058] Fig.10 It is a comparison diagram of the volatilization curves of free eugenol, L-lysine and eugenol cocrystal, free cinnamaldehyde, and L-lysine and cinnamaldehyde cocrystal;
[0059] Fig.11 This is a comparison chart of the inhibitory effects of free eugenol, L-lysine and eugenol co-crystal on Escherichia coli in tomato juice. DETAILED DESCRIPTION
[0060] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0061] The detection instruments and methods involved in the following embodiments include:
[0062] 1. X-ray powder diffraction analysis: using Rigaku MiniFlex 600 diffractometer from Rigaku Co., Ltd., Cu-Kα ray The voltage was 40 kV, the current was 150 mA, the step size was 0.01°, the scanning speed was 20° / min, the scanning range was 3.0-40.0°, and the test temperature was room temperature;
[0063] 2. Differential Scanning Calorimetry (DSC): The samples were tested using a DSC 214 differential calorimeter from NETZSCH Scientific Instruments Co., Ltd. The atmosphere was nitrogen and the heating rate was 10°C / min.
[0064] 3. Infrared spectrum analysis: Bruker Vertex 7 Fourier transform infrared spectrometer was used for detection, with a detection range of 4000-500cm -1 , resolution 0.2cm -1 , data were collected at room temperature.
[0065] Example 1
[0066] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0067] Weigh 2 mmol L-lysine and 2 mmol eugenol, add them into a ball mill together with a steel ball with a diameter of 1 cm, and grind at a frequency of 20 Hz for 30 minutes to obtain an off-white powder of L-lysine and eugenol cocrystal.
[0068] The L-lysine and eugenol cocrystal prepared in Example 1 was subjected to X-ray powder diffraction analysis. Figure 1 is the X-ray powder diffraction pattern of the L-lysine and eugenol cocrystal in Example 1. The X-ray powder diffraction analysis data are shown in Table 1:
[0069] Table 1 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 1
[0070]
[0071] The L-lysine and eugenol cocrystal prepared in Example 1 was subjected to differential scanning calorimetry analysis. Figure 2is the differential scanning calorimetry analysis diagram of the L-lysine and eugenol cocrystal in Example 1, Figure 2 It can be seen that the co-crystal of L-lysine and eugenol exhibits an endothermic peak at about 101°C.
[0072] The L-lysine and eugenol cocrystal prepared in Example 1 was analyzed by Fourier transform infrared spectroscopy. Figure 3 is the Fourier transform infrared spectrum of the L-lysine and eugenol cocrystal in Example 1, Figure 3 It can be seen that the eugenol ... -1 、3369cm -1 、3037cm -1 、2935cm -1 、2865cm -1 、2824cm -1 、2680m -1 、2368cm -1 、2128cm -1 、1829cm -1 、1639cm -1 、1584cm -1 、1552cm -1 、1497cm -1 、1466cm -1 、1415cm -1 、1359cm -1 、1355cm -1 、1328cm -1 、1274cm -1 、1251cm -1 、1189cm -1 、1155cm -1 、1077cm -1 、1040cm -1 、993cm -1 、951cm -1 、909cm -1 、850cm -1 、805cm -1 、745cm -1 、693cm -1 、640cm -1 、586cm -1 、544cm -1 There are characteristic peaks.
[0073] Example 2
[0074] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0075] Weigh 0.2 mmol L-lysine and 0.2 mmol eugenol, add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, add 5 μL methyl tert-butyl ether, and grind at a frequency of 20 Hz for 30 min to obtain an off-white powder of L-lysine and eugenol cocrystal.
[0076] The L-lysine and eugenol cocrystal prepared in Example 2 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 2:
[0077] Table 2 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 2
[0078]
[0079] Example 3
[0080] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0081] Weigh 0.2 mmol L-lysine and 0.2 mmol eugenol, add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, add 5 μL acetone, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine and eugenol cocrystal.
[0082] The L-lysine and eugenol cocrystal prepared in Example 3 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 3:
[0083] Table 3 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 3
[0084]
[0085]
[0086] Example 4
[0087] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0088] Weigh 0.2 mmol L-lysine and 0.2 mmol eugenol, add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, add 5 μL of n-hexane, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine and eugenol cocrystal.
[0089] The L-lysine and eugenol cocrystal prepared in Example 4 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 4:
[0090] Table 4 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 4
[0091]
[0092] Example 5
[0093] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0094] Weigh 0.2 mmol L-lysine and 0.2 mmol eugenol into a 10 mL EP tube, add 1 mL ethyl acetate, and stir at 600 rpm for 12 h at room temperature. Filter the suspension under reduced pressure, and dry the filter cake at room temperature for 24 h to obtain an off-white powder of L-lysine and eugenol cocrystal.
[0095] The L-lysine and eugenol cocrystal prepared in Example 5 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 5:
[0096] Table 5 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 5
[0097]
[0098] Example 6
[0099] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0100] Weigh 0.2 mmol L-lysine and 0.2 mmol eugenol into a 10 mL EP tube, add 1 mL n-heptane, and stir at 600 rpm for 6 h at room temperature. Filter the suspension under reduced pressure, and dry the filter cake at room temperature for 24 h to obtain an off-white powder of L-lysine and eugenol cocrystal.
[0101] The L-lysine and eugenol cocrystal prepared in Example 6 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 6:
[0102] Table 6 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 6
[0103]
[0104]
[0105] Example 7
[0106] In this embodiment, a co-crystal of L-lysine and eugenol is prepared by the following steps:
[0107] Weigh 0.2 mol L-lysine and 0.2 mol eugenol into a grinder and grind for 2 minutes to obtain an off-white powder of L-lysine and eugenol eugenol cocrystal.
[0108] The L-lysine and eugenol cocrystal prepared in Example 7 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 7:
[0109] Table 7 X-ray powder diffraction analysis data of L-lysine and eugenol cocrystal in Example 7
[0110]
[0111] Example 8
[0112] This embodiment prepares a L-lysine and eugenol composition, and the steps are:
[0113] 0.4 mmol L-lysine and 0.2 mmol eugenol were weighed, added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and eugenol.
[0114] The L-lysine and eugenol composition prepared in Example 8 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 8:
[0115] Table 8 X-ray powder diffraction analysis data of the composition of L-lysine and eugenol in Example 8
[0116]
[0117]
[0118] It can be seen from the X-ray powder diffraction analysis data in Table 8 that the L-lysine and eugenol composition has characteristic peaks of the above-mentioned L-lysine and eugenol co-crystals at 2θ angles of approximately 4.8°, 9.8°, 13.5°, 14.8°, 17.6°, 22.0°, and 25.0°, and characteristic peaks of L-lysine at 2θ angles of approximately 4.8°, 18.5°, 19.5°, and 20.4°, indicating that the composition is composed of L-lysine and eugenol co-crystals and L-lysine.
[0119] Example 9
[0120] This embodiment prepares a L-lysine and eugenol composition, and the steps are:
[0121] 0.6 mmol L-lysine and 0.2 mmol eugenol were weighed, added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and eugenol.
[0122] The L-lysine and eugenol composition prepared in Example 9 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 9:
[0123] Table 9 X-ray powder diffraction analysis data of the composition of L-lysine and eugenol in Example 9
[0124]
[0125] It can be seen from the X-ray powder diffraction analysis data in Table 9 that the L-lysine and eugenol composition has characteristic peaks of the above-mentioned L-lysine and eugenol co-crystals at 2θ angles of approximately 4.9°, 10.0°, 13.6°, 14.9°, 17.6°, 22.1°, and 25.0°, and characteristic peaks of L-lysine at 2θ angles of approximately 4.9°, 18.5°, 19.5°, and 20.4°, indicating that the composition is composed of L-lysine and eugenol co-crystals and L-lysine.
[0126] Example 10
[0127] This embodiment prepares a L-lysine and eugenol composition, and the steps are:
[0128] 0.5 mmol L-lysine and 0.1 mmol eugenol were weighed, added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and eugenol.
[0129] The L-lysine and eugenol composition prepared in Example 10 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 10:
[0130] Table 10 X-ray powder diffraction analysis data of the composition of L-lysine and eugenol in Example 10
[0131]
[0132] It can be seen from the X-ray powder diffraction analysis data in Table 10 that the L-lysine and eugenol composition has characteristic peaks of the above-mentioned L-lysine and eugenol co-crystals at 2θ angles of approximately 4.8°, 10.0°, 13.6°, 14.8°, 17.6°, 22.0°, and 25.0°, and characteristic peaks of L-lysine at 2θ angles of approximately 4.8°, 18.4°, 19.4°, and 20.3°, indicating that the composition is composed of L-lysine and eugenol co-crystals and L-lysine.
[0133] Embodiment 11
[0134] This embodiment prepares a L-lysine and eugenol composition, and the steps are:
[0135] 0.9 mmol L-lysine and 0.1 mmol eugenol were weighed, added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and eugenol.
[0136] The L-lysine and eugenol composition prepared in Example 11 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 11:
[0137] Table 11 X-ray powder diffraction analysis data of the composition of L-lysine and eugenol in Example 11
[0138]
[0139]
[0140] It can be seen from the X-ray powder diffraction analysis data in Table 11 that the L-lysine and eugenol composition has characteristic peaks of the above-mentioned L-lysine and eugenol co-crystal at 2θ angles of approximately 4.9°, 10.0°, 14.8°, and 25.0°, and characteristic peaks of L-lysine at 2θ angles of approximately 4.9°, 18.5°, 19.5°, and 20.4°, indicating that the composition is composed of L-lysine and eugenol co-crystal and L-lysine.
[0141] Example 12
[0142] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0143] Weigh 2 mmol L-lysine and 2 mmol cinnamaldehyde, add them together with a steel ball with a diameter of 1 cm into a ball mill, grind at a frequency of 20 Hz for 30 minutes, and obtain an off-white powder of L-lysine and cinnamaldehyde eutectic.
[0144] The L-lysine and cinnamaldehyde cocrystal obtained in Example 12 was subjected to X-ray powder diffraction analysis. Figure 4 is the X-ray powder diffraction pattern of the L-lysine and cinnamaldehyde cocrystal in Example 12. The X-ray powder diffraction analysis data are shown in Table 12:
[0145] Table 12 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 12
[0146]
[0147] The L-lysine and cinnamaldehyde cocrystal prepared in Example 12 was subjected to differential scanning calorimetry analysis. Figure 5 is the differential scanning calorimetry analysis diagram of the L-lysine and cinnamaldehyde cocrystal in Example 12, Figure 5 It can be seen that the co-crystal of L-lysine and cinnamaldehyde has endothermic peaks at about 112°C and about 145°C.
[0148] The L-lysine and cinnamaldehyde cocrystal obtained in Example 12 was analyzed by Fourier transform infrared spectroscopy. Figure 6 is the Fourier transform infrared spectrum of the L-lysine and cinnamaldehyde cocrystal in Example 12, Figure 6 It can be seen that the eutectic of L-lysine and cinnamaldehyde is at 3425 cm -1 、3051cm -1 、2924cm -1 、2861cm -1 、2818cm -1 、2747cm -1 、2617cm -1 、2386cm -1 、2131cm -1 、1948cm -1 、1886cm -1 、1813cm -1 、1580cm -1 、1499cm -1 、1406cm -1 、1357cm -1 、1319cm -1 、1253cm -1 、1181cm -1 、1144cm -1 、1074cm -1 、1022cm -1 、978cm -1 、957cm -1 、922cm -1 、847cm -1 、802cm -1、744cm -1 、692cm -1 、664cm -1 、596cm -1 、557cm -1 、540cm -1 There are characteristic peaks.
[0149] Example 13
[0150] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0151] Weigh 0.2 mmol L-lysine and 0.2 mmol cinnamaldehyde, add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, add 5 μL ethanol, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine and cinnamaldehyde cocrystal.
[0152] The L-lysine and cinnamaldehyde cocrystal obtained in Example 13 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 13:
[0153] Table 13 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 13
[0154]
[0155] Embodiment 14
[0156] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0157] Weigh 0.2 mmol L-lysine and 0.2 mmol cinnamaldehyde, add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, add 5 μL n-heptane, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine and cinnamaldehyde cocrystal.
[0158] The L-lysine and cinnamaldehyde cocrystal obtained in Example 14 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 14:
[0159] Table 14 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 14
[0160]
[0161] Embodiment 15
[0162] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0163] Weigh 0.2 mmol L-lysine and 0.2 mmol cinnamaldehyde into a 10 mL EP tube, add 1 mL methanol, and stir at 600 rpm for 6 h at room temperature. Filter the suspension under reduced pressure, and dry the filter cake at room temperature for 24 h to obtain an off-white powder of L-lysine and cinnamaldehyde cocrystal.
[0164] The L-lysine and cinnamaldehyde cocrystal obtained in Example 15 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 15:
[0165] Table 15 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 15
[0166]
[0167] Example 16
[0168] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0169] Weigh 0.2 mmol L-lysine and 0.2 mmol cinnamaldehyde into a 10 mL EP tube, add 1 mL isopropanol, and stir at 600 rpm for 12 h at room temperature. Filter the suspension under reduced pressure, and dry the filter cake at room temperature for 24 h to obtain an off-white powder of L-lysine and cinnamaldehyde cocrystal.
[0170] The L-lysine and cinnamaldehyde cocrystal obtained in Example 16 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 16:
[0171] Table 16 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 16
[0172]
[0173] Embodiment 17
[0174] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0175] Weigh 0.2 mmol L-lysine and 0.2 mmol cinnamaldehyde into a 10 mL EP tube, add 1 mL n-hexane, and stir at 600 rpm for 6 h at room temperature. Filter the suspension under reduced pressure, and dry the filter cake at room temperature for 24 h to obtain an off-white powder of L-lysine and cinnamaldehyde cocrystal.
[0176] The L-lysine and cinnamaldehyde cocrystal obtained in Example 17 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 17:
[0177] Table 17 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 17
[0178]
[0179] Embodiment 18
[0180] In this embodiment, a co-crystal of L-lysine and cinnamaldehyde is prepared by the following steps:
[0181] Weigh 0.2 mol of L-lysine and 0.2 mol of cinnamaldehyde into a grinder and grind for 2 minutes to obtain a light yellow powder of L-lysine and cinnamaldehyde eutectic.
[0182] The L-lysine and cinnamaldehyde cocrystal obtained in Example 18 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 18:
[0183] Table 18 X-ray powder diffraction analysis data of L-lysine and cinnamaldehyde cocrystal in Example 18
[0184]
[0185] Embodiment 19
[0186] This embodiment prepares a composition of L-lysine and cinnamaldehyde, and the steps are:
[0187] 0.4 mmol L-lysine and 0.2 mmol cinnamaldehyde were weighed and added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and cinnamaldehyde.
[0188] The L-lysine and cinnamaldehyde composition prepared in Example 19 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 19:
[0189] Table 19 X-ray powder diffraction analysis data of the composition of L-lysine and cinnamaldehyde in Example 19
[0190]
[0191] It can be seen from the X-ray powder diffraction analysis data in Table 19 that the L-lysine and cinnamaldehyde composition has characteristic peaks of the above-mentioned L-lysine and cinnamaldehyde cocrystals at 2θ angles of approximately 5.4°, 8.2°, 13.9°, 16.7°, 19.5°, 19.9°, and 22.3°, and has characteristic peaks of L-lysine at 2θ angles of approximately 4.9°, 18.5°, 19.5°, and 20.4°, indicating that the composition is composed of L-lysine and cinnamaldehyde cocrystals and L-lysine.
[0192] Embodiment 20
[0193] This embodiment prepares a composition of L-lysine and cinnamaldehyde, and the steps are:
[0194] 0.6 mmol L-lysine and 0.2 mmol cinnamaldehyde were weighed and added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm, and ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a composition of L-lysine and cinnamaldehyde.
[0195] The L-lysine and cinnamaldehyde composition prepared in Example 20 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 20:
[0196] Table 20 X-ray powder diffraction analysis data of the composition of L-lysine and cinnamaldehyde in Example 20
[0197]
[0198] It can be seen from the X-ray powder diffraction analysis data in Table 20 that the L-lysine and cinnamaldehyde composition has characteristic peaks of the above-mentioned L-lysine and cinnamaldehyde cocrystal at 2θ angles of approximately 5.4°, 8.4°, 19.4°, and 19.9°, and has characteristic peaks of L-lysine at 2θ angles of approximately 4.9°, 18.5°, and 19.4°, indicating that the composition is composed of L-lysine and cinnamaldehyde cocrystal and L-lysine.
[0199] Embodiment 21
[0200] In this embodiment, a co-crystal of L-lysine, eugenol and cinnamaldehyde is prepared by the following steps:
[0201] Weigh 0.4 mmol L-lysine, 0.2 mmol eugenol, and 0.2 mmol cinnamaldehyde, and add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine, eugenol, and cinnamaldehyde cocrystal.
[0202] The L-lysine, eugenol and cinnamaldehyde cocrystals prepared in Example 21 were subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 21:
[0203] Table 21 X-ray powder diffraction analysis data of L-lysine, eugenol and cinnamaldehyde cocrystal in Example 21
[0204]
[0205] Embodiment 22
[0206] In this embodiment, a co-crystal of L-lysine, eugenol and cinnamaldehyde is prepared by the following steps:
[0207] Weigh 0.6 mmol L-lysine, 0.4 mmol eugenol, and 0.2 mmol cinnamaldehyde, and add them together with a steel ball with a diameter of 5 mm into a 2 mL EP tube, grind at a frequency of 20 Hz for 30 min, and obtain an off-white powder of L-lysine, eugenol, and cinnamaldehyde cocrystal.
[0208] X-ray powder diffraction analysis was performed on the cocrystal of L-lysine, eugenol and cinnamaldehyde obtained in Example 22. Figure 7 is the X-ray powder diffraction pattern of the co-crystal of L-lysine, eugenol and cinnamaldehyde in Example 22. The X-ray powder diffraction analysis data are shown in Table 22:
[0209] Table 22 X-ray powder diffraction analysis data of L-lysine, eugenol and cinnamaldehyde cocrystal in Example 22
[0210]
[0211]
[0212] Embodiment 23
[0213] In this embodiment, a co-crystal of L-lysine, eugenol and cinnamaldehyde is prepared by the following steps:
[0214] 1.0 mmol L-lysine, 0.8 mmol eugenol, and 0.2 mmol cinnamaldehyde were weighed and added into a 2 mL EP tube together with a steel ball with a diameter of 5 mm. The mixture was ground at a frequency of 20 Hz for 30 min to obtain an off-white powder of a cocrystal of L-lysine, eugenol, and cinnamaldehyde.
[0215] The L-lysine, eugenol and cinnamaldehyde cocrystals prepared in Example 23 were subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 23:
[0216] Table 23 X-ray powder diffraction analysis data of L-lysine, eugenol and cinnamaldehyde cocrystal in Example 23
[0217]
[0218] Embodiment 24
[0219] In this embodiment, a co-crystal of L-lysine, eugenol and cinnamaldehyde is prepared by the following steps:
[0220] Weigh 3 mmol L-lysine, 1 mmol eugenol, and 2 mmol cinnamaldehyde, add them together with a steel ball with a diameter of 1 cm into a ball mill, grind at a frequency of 20 Hz for 30 minutes, and obtain an off-white powder of L-lysine, eugenol and cinnamaldehyde eutectic.
[0221] The L-lysine, eugenol and cinnamaldehyde cocrystals prepared in Example 24 were subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 24:
[0222] Table 24 X-ray powder diffraction analysis data of L-lysine, eugenol and cinnamaldehyde cocrystal in Example 24
[0223]
[0224] Embodiment 25
[0225] In this embodiment, a co-crystal of L-lysine, eugenol and cinnamaldehyde is prepared by the following steps:
[0226] Weigh 5 mmol L-lysine, 1 mmol eugenol, and 4 mmol cinnamaldehyde, add them together with a steel ball with a diameter of 1 cm into a ball mill, grind at a frequency of 20 Hz for 30 minutes, and obtain an off-white powder of L-lysine, eugenol and cinnamaldehyde eutectic.
[0227] The L-lysine, eugenol and cinnamaldehyde cocrystal prepared in Example 25 was subjected to X-ray powder diffraction analysis. The X-ray powder diffraction analysis data are shown in Table 25:
[0228] Table 25 X-ray powder diffraction analysis data of L-lysine, eugenol and cinnamaldehyde cocrystal in Example 25
[0229]
[0230] In addition, the present invention also attempts to react active ingredients of plant essential oils such as eugenol and cinnamaldehyde with proline, leucine, isoleucine, histidine, methionine, phenylalanine, threonine, tryptophan, valine, glutamic acid, arginine, aspartic acid, cystine, pyroglutamic acid, serine, glycine, tyrosine, etc. through eutectic technology, and it is found that they are unable to form eutectics with active ingredients of plant essential oils such as eugenol and cinnamaldehyde.
[0231] Hygroscopicity evaluation
[0232] The powder samples of L-lysine and eugenol cocrystal prepared in Example 1 and L-lysine and cinnamaldehyde cocrystal prepared in Example 12 were ground and passed through 100 mesh and 200 mesh sieves respectively, and the particle size was controlled to be 75 μm-150 μm, and L-lysine with the same particle size was used as a comparison. The DVS Intrinsic dynamic moisture adsorption instrument of SMS Company of the United Kingdom was used, the temperature was kept constant at 25°C, and then the relative humidity was controlled to increase gradually from 10% to 80%, and the mass change of each relative humidity sample after the moisture absorption and weight gain reached equilibrium was recorded. The experimental results are shown in Table 26.
[0233] Table 26 Evaluation results of hygroscopicity of cocrystal and L-lysine
[0234]
[0235]
[0236] Table 26 shows the evaluation results of the hygroscopicity of the eutectic and L-lysine in Example 1 and Example 12. It can be seen from Table 26 that pure L-lysine has strong hygroscopicity. In the process of increasing the relative humidity from 10% to 80%, the weight gain percentage of L-lysine increases from 5.75% to 77.87%. The weight gain percentage of the eutectic of L-lysine and eugenol in Example 1 is 6.82% when the relative humidity reaches 80%, which is similar to the weight gain percentage of pure L-lysine at 40% relative humidity. The weight gain percentage of the eutectic of L-lysine and cinnamaldehyde in Example 12 is only 2.47% when the relative humidity reaches 80%, which is lower than the weight gain percentage of pure L-lysine at 10% relative humidity. It can be seen that after forming a eutectic with eugenol or cinnamaldehyde, its hygroscopicity is greatly reduced.
[0237] Stability evaluation
[0238] The powder samples of L-lysine and eugenol cocrystal prepared in Example 1 and L-lysine and cinnamaldehyde cocrystal prepared in Example 12 were ground and passed through 100 mesh and 200 mesh sieves respectively to control the particle size to be 75 μm-150 μm. The above powder samples were sealed in PV bags and placed under accelerated stability conditions of 40°C / 75%RH. The crystal phase was detected by X-ray powder diffraction analysis after 1 month, 2 months, and 3 months respectively. Figure 8 is an X-ray powder diffraction spectrum of the L-lysine and eugenol co-crystal in Example 1 placed under accelerated stability conditions of 40° C. / 75% RH for 1-3 months; Fig. 9 is the X-ray powder diffraction spectrum of the L-lysine and cinnamaldehyde cocrystal in Example 12 after being placed under accelerated stability conditions of 40°C / 75%RH for 1-3 months. Figure 8 and Fig. 9 It can be seen that the cocrystals of L-lysine and eugenol and the cocrystals of L-lysine and cinnamaldehyde have good stability.
[0239] Volatility evaluation
[0240] The powder samples of L-lysine and eugenol cocrystal prepared in Example 1 and L-lysine and cinnamaldehyde cocrystal prepared in Example 12 were ground and passed through 100 mesh and 200 mesh sieves respectively to control the particle size between 75 μm and 150 μm. Weigh 100.0 mg of powder samples of L-lysine and eugenol cocrystal, L-lysine and cinnamaldehyde cocrystal, free eugenol and free cinnamaldehyde respectively, place them in 10 mL glass beakers, openly place them in a thermostat (30°C ± 0.4°C), weigh them at 1, 3, 5, 7, 10, 20 and 30 days, and repeat each test three times. Plot the sample volatility evaluation curve with time as the horizontal axis and mass as the vertical axis. Fig.10 The volatilization curves of free eugenol, L-lysine and eugenol cocrystal, free cinnamaldehyde, L-lysine and cinnamaldehyde cocrystal are compared. Fig.10 It can be seen that free eugenol and free cinnamaldehyde volatilize rapidly, with the residual masses of the two being 17.0% and 21.9% respectively within 10 days, and both completely volatilize within 30 days. In contrast, the volatilization rate of L-lysine and eugenol cocrystals and L-lysine and cinnamaldehyde cocrystals is significantly reduced, with the residual masses of the two being 91.1% and 94.8% respectively on the 30th day. This indicates that the L-lysine and eugenol cocrystals and L-lysine and cinnamaldehyde cocrystals prepared by the present invention have lower volatility and a longer retention time of the active ingredients.
[0241] Antibacterial test
[0242] The powder samples of L-lysine and eugenol eutectic prepared in Example 1 and L-lysine and cinnamaldehyde eutectic prepared in Example 12 were ground and passed through 100 mesh and 200 mesh sieves respectively to control the particle size to be 75 μm-150 μm. Eugenol, cinnamaldehyde, L-lysine and eugenol eutectic powder samples and L-lysine and cinnamaldehyde eutectic powder samples were prepared into standard solutions with concentrations of 8.0, 4.0, 2.0, 1.0, 0.50, 0.25, 0.10, and 0.05 mg / mL by microdilution method, and Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, melanin, aflatoxin, fumagillin and Penicillium roqueforti were taken as antibacterial objects. The minimum inhibitory concentration was determined according to the micro-broth method recommended by the American Clinical and Laboratory Standards Association: the above solutions of different concentrations were added to a 96-well plate, and each well finally contained 100 μL of plant essential oil active ingredient / plant essential oil active ingredient eutectic dilution and 100 μL of 5×10 5 cfu / mL of diluted bacterial suspension was placed in a 37°C incubator for 24 hours, and each group of experiments was repeated 3 times. The lowest antibacterial concentration for sterile growth was recorded as the MIC value, and its ultraviolet absorption OD value was measured by an enzyme marker. The experimental results are shown in Table 27.
[0243] Table 27 Minimum inhibitory concentration (MIC-mg / mL) of active ingredients in plant essential oils and their co-crystals
[0244] Fungus name Eugenol Cocrystal of L-lysine and eugenol Cinnamaldehyde Cocrystal of L-lysine and cinnamaldehyde Escherichia coli 2.0 1.0 0.25 0.25 Staphylococcus aureus 2.0 1.0 0.50 0.25 Salmonella Enteritidis 2.0 1.0 0.50 0.25 Candida albicans 2.0 1.0 0.50 0.25 Melanocin 0.25 0.10 0.25 0.10 Aspergillus flavus 8.0 4.0 4.0 2.0 Aspergillus fumigatus 8.0 4.0 4.0 2.0 Penicillium roqueforti 0.25 0.10 0.10 0.05
[0245] Table 27 shows the minimum inhibitory concentration of the active ingredients of plant essential oils and their cocrystals. It can be seen from Table 27 that, compared with free eugenol, the cocrystals of L-lysine and eugenol have lower minimum inhibitory concentrations against Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Candida albicans, mesina, Aspergillus fumigatus, Aspergillus fumigatus, and Penicillium roqueforti; compared with free cinnamaldehyde, the cocrystals of L-lysine and cinnamaldehyde have lower minimum inhibitory concentrations against Staphylococcus aureus, Salmonella enteritidis, Candida albicans, mesina, Aspergillus fumigatus, Aspergillus fumigatus, and Penicillium roqueforti, while the minimum inhibitory concentrations against Escherichia coli are comparable. This indicates that the cocrystals provided by the present invention have better antibacterial effects than free active ingredients of plant essential oils and can be used as antibacterial agents.
[0246] Antibacterial test of tomato juice
[0247] Eugenol and the cocrystal of L-lysine and eugenol in Example 1 were selected to compare their antibacterial effects on Escherichia coli in tomato juice. Fresh tomatoes were selected, cleaned and peeled, and tomato juice was extracted using a juicer. The extracted tomato juice was filtered to remove the residue to obtain clarified tomato juice. The tomato juice was pasteurized (65°C, 30min) and then inoculated with Escherichia coli and stored at 4°C. The tomato juice was treated with three different methods: 1) Control group: no antibacterial substances were added; 2) Experimental group 1: free eugenol was added to tomato juice (concentration of 1.0 mg / mL); 3) Experimental group 2: L-lysine and eugenol cocrystal in Example 1 (concentration of 2.0 mg / mL, of which the concentration of eugenol was 1.0 mg / mL) was added to tomato juice. The number of Escherichia coli in tomato juice was determined by plate colony counting method on days 0, 1, 3, 5 and 7.
[0248] Fig.11 This is a comparison of the inhibitory effects of free eugenol, L-lysine and eugenol cocrystal on Escherichia coli in tomato juice. Fig.11 It can be seen that at all time points, the number of Escherichia coli is ranked as follows: control group > experimental group 1 > experimental group 2. This indicates that the antibacterial effect of the co-crystal of L-lysine and eugenol on Escherichia coli is significantly better than that of free eugenol. This indicates that the antibacterial effect of the co-crystal prepared by the present invention is significantly better than that of the free active ingredient of plant essential oil.
[0249] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be thought of by any technician familiar with the field within the technical scope disclosed by the present invention without creative work should be covered within the protection scope of the present invention.
Claims
1. A eutectic, characterized in that: The preparation method comprises the following raw materials: L-lysine and active ingredients of plant essential oil; the molar ratio of L-lysine to the active ingredients of plant essential oil is 1:1; and the active ingredients of plant essential oil are at least one of eugenol and cinnamaldehyde.
2. The eutectic according to claim 1, characterized in that When the active ingredient of the plant essential oil is eugenol, the cocrystal is a cocrystal of L-lysine and eugenol; the cocrystal of L-lysine and eugenol has diffraction peaks at 2θ values of 4.8±0.2°, 9.8±0.2°, 13.6±0.2°, 14.8±0.2°, 17.5±0.2°, 22.0±0.2°, and 24.9±0.2° in the X-ray powder diffraction spectrum.
3. The eutectic according to claim 2, characterized in that The L-lysine and eugenol co-crystal also has at least one diffraction peak at 2θ values of 10.5±0.2°, 19.8±0.2°, 21.1±0.2°, 21.3±0.2°, 23.6±0.2°, 25.9±0.2°, 31.6±0.2°, and 36.6±0.2° in the X-ray powder diffraction spectrum.
4. The eutectic according to claim 1, characterized in that When the active ingredient of the plant essential oil is cinnamaldehyde, the cocrystal is a cocrystal of L-lysine and cinnamaldehyde; the cocrystal of L-lysine and cinnamaldehyde has diffraction peaks at 2θ values of 5.4±0.2°, 8.1±0.2°, 13.7±0.2°, 16.6±0.2°, 19.3±0.2°, 19.8±0.2°, and 22.2±0.2° in the X-ray powder diffraction spectrum.
5. The eutectic according to claim 4, characterized in that The L-lysine and cinnamaldehyde cocrystal also has at least one diffraction peak at 2θ values of 11.0±0.2°, 18.4±0.2°, 20.9±0.2°, 25.2±0.2°, 28.0±0.2°, and 32.8±0.2° in the X-ray powder diffraction spectrum.
6. The eutectic according to claim 1, characterized in that When the active ingredients of the plant essential oil are eugenol and cinnamaldehyde, the cocrystal is a cocrystal of L-lysine, eugenol and cinnamaldehyde; the molar ratio of the eugenol to cinnamaldehyde is 1:(0.25-4); the cocrystal of L-lysine, eugenol and cinnamaldehyde has diffraction peaks at 2θ values of 4.8±0.2°, 5.4±0.2°, 8.1±0.2°, 14.8±0.2°, 22.0±0.2° and 24.9±0.2° in the X-ray powder diffraction spectrum.
7. The eutectic according to claim 6, characterized in that The L-lysine, eugenol and cinnamaldehyde co-crystal also has at least one diffraction peak at 2θ values of 9.8±0.2°, 10.5±0.2°, 13.7±0.2°, 16.6±0.2°, 17.5±0.2°, 19.3±0.2°, 19.8±0.2°, 21.1±0.2°, 21.3±0.2°, 22.2±0.2°, 23.6±0.2°, 25.9±0.2°, 31.6±0.2°, and 36.6±0.2° in the X-ray powder diffraction spectrum.
8. The method for preparing a co-crystal according to any one of claims 1 to 7, characterized in that: The preparation method comprises any one of the following two methods: Method 1: mixing the L-lysine and the active ingredient of the plant essential oil under solvent conditions, and collecting the solid by solid-liquid separation to obtain the co-crystal; Method 2: Applying mechanical force to make the L-lysine contact and react with the active ingredient of plant essential oil to obtain the co-crystal.
9. An antibacterial agent, characterized in that The co-crystal comprises the co-crystal according to any one of claims 1 to 7.
10. Use of the antibacterial agent according to claim 9 in food, health products, feed, daily chemicals, medicines and pesticides.
Citation Information
Patent Citations
Animal feed composition
CN101331915A
Pig feed additive with pork quality improvement function and preparation method
CN105494980A
Additive composition capable of improving sow postpartum body condition or reproductive performance of sows and preparing method of additive composition
CN106721305A
Co-crystal of carvacrol and L-lysine as well as preparation method and application of co-crystal
CN117924043A
Eutectic of thymol and L-lysine as well as preparation method and application thereof
CN118026820A